La intermediación en el sector agrícola ecuatoriano y su impacto en el comercio justo - Quezada Eugenio, Daysi Karina (2022)
Fair Trade has been defined from several angles, it is first of all a movement that fights for equality in the agricultural sector, it is a business vision, it is a fair marketing practice, it is part of the economic system of Ecuador, it is equitable and transparent, but that its practice is limited by factors such as intermediation and other monopolistic practices that affect the agricultural economy of rural sectors, preventing personal economic development. Large-scale producers have all the facilities to increase their production and profits, even maintaining excellent relations with government entities, but little or nothing is done in the face of the problem that implies an evident degree of social inequality as a result of intermediary practices that generate an economic imbalance in small producers. The investigation establishes that fair trade mainly affects cocoa producers in agricultural sectors such as in the Balao canton. The social and economic impact of intermediation affects producers who are not part of Fair Trade associations even more, given that they are affected to a greater extent in the negotiation of the price of agricultural products, it is necessary that it be included in the national regulatory framework clear rules that go from the definition of Fair Trade and what must be done to achieve said model, which must be based on the application of the objectives of Fair Trade and the successful models of the United States and Europe.